Indonesia–United States Military Cooperation in Capacity Building through the Garuda Shield Exercise - Natalia Nadeak; Raihan Tara Hanita (Universitas Budi Luhur, 2026)
Abstract: This article examines Indonesia–United States military cooperation in the context of capacity building through the Garuda Shield joint military exercise conducted between 2019 and 2022. Situated within the evolving Indo-Pacific security environment, the study explores how defence cooperation functions not only as a military training mechanism but also as an instrument of defence diplomacy and confidence building. Employing a qualitative descriptive research design, this study draws on secondary data sources including official government documents, defence policy papers, academic literature, and credible international media reports. The analysis is guided by realism, national interest theory, defence diplomacy, and confidence-building measures. The findings demonstrate that Garuda Shield significantly enhances military interoperability, operational readiness, and professional competence within the Indonesian Army, while simultaneously strengthening strategic trust between Indonesia and the United States. Moreover, the transformation of Garuda Shield into a multinational exercise in 2022 reflects increasing regional and international confidence in Indonesia’s role as a stabilizing middle power in the Indo-Pacific. This article argues that Garuda Shield constitutes a strategic instrument of defence diplomacy that reinforces Indonesia’s free and active foreign policy, enabling Indonesia to navigate intensifying great-power competition while maintaining strategic autonomy and contributing to a more inclusive regional security architecture. Abstrak: Abstrak: Artikel ini mengkaji kerja sama militer Indonesia–Amerika Serikat dalam konteks pembangunan kapasitas melalui latihan militer bersama Garuda Shield yang dilaksanakan antara tahun 2019 dan 2022. Terletak dalam lingkungan keamanan Indo-Pasifik yang terus berkembang, studi ini mengeksplorasi bagaimana kerja sama pertahanan tidak hanya berfungsi sebagai mekanisme pelatihan militer tetapi juga sebagai instrumen diplomasi pertahanan dan pembangunan kepercayaan. Menggunakan desain penelitian deskriptif kualitatif, penelitian ini mengandalkan sumber data sekunder termasuk dokumen resmi pemerintah, makalah kebijakan pertahanan, literatur akademis, dan laporan media internasional yang kredibel. Analisis ini dipandu oleh realisme, teori kepentingan nasional, diplomasi pertahanan, dan langkah-langkah membangun kepercayaan. Temuan ini menunjukkan bahwa Garuda Shield secara signifikan meningkatkan interoperabilitas militer, kesiapan operasional, dan kompetensi profesional dalam Angkatan Darat Indonesia, sekaligus memperkuat kepercayaan strategis antara Indonesia dan Amerika Serikat. Selain itu, transformasi Garuda Shield menjadi latihan multinasional pada tahun 2022 mencerminkan meningkatnya kepercayaan regional dan internasional terhadap peran Indonesia sebagai kekuatan menengah yang menstabilkan di Indo-Pasifik. Artikel ini berpendapat bahwa Garuda Shield berfungsi sebagai instrumen strategis diplomasi pertahanan, memperkuat kebijakan luar negeri Indonesia yang bebas dan aktif. Hal ini memungkinkan Indonesia untuk menavigasi persaingan kekuatan besar yang semakin intensif sambil mempertahankan otonomi strategis dan berkontribusi pada arsitektur keamanan regional yang lebih inklusif.